If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + 3(z + -2) = 7z + -3(z + -10) Reorder the terms: 3z + 3(-2 + z) = 7z + -3(z + -10) 3z + (-2 * 3 + z * 3) = 7z + -3(z + -10) 3z + (-6 + 3z) = 7z + -3(z + -10) Reorder the terms: -6 + 3z + 3z = 7z + -3(z + -10) Combine like terms: 3z + 3z = 6z -6 + 6z = 7z + -3(z + -10) Reorder the terms: -6 + 6z = 7z + -3(-10 + z) -6 + 6z = 7z + (-10 * -3 + z * -3) -6 + 6z = 7z + (30 + -3z) Reorder the terms: -6 + 6z = 30 + 7z + -3z Combine like terms: 7z + -3z = 4z -6 + 6z = 30 + 4z Solving -6 + 6z = 30 + 4z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-4z' to each side of the equation. -6 + 6z + -4z = 30 + 4z + -4z Combine like terms: 6z + -4z = 2z -6 + 2z = 30 + 4z + -4z Combine like terms: 4z + -4z = 0 -6 + 2z = 30 + 0 -6 + 2z = 30 Add '6' to each side of the equation. -6 + 6 + 2z = 30 + 6 Combine like terms: -6 + 6 = 0 0 + 2z = 30 + 6 2z = 30 + 6 Combine like terms: 30 + 6 = 36 2z = 36 Divide each side by '2'. z = 18 Simplifying z = 18
| (2x)(6x)= | | z+0.2=0.6(z+3) | | 5.2q-4.5-5.6q=-1.4q-3.7 | | x^2+6x-76=-4 | | 1/2*x=-4 | | X-y-2=2z | | Sin(5x)-tan(5x)=0 | | (10s^2+5)-(5s^2+3s-2)=0 | | 4(z-6)+2z=6(z+4)-48 | | Sinx-tanx=0 | | 9x+6y=152 | | z-4=-9z-4 | | -15=x+23 | | 8(z+6)=7(z-7)+z | | 4x+6y=37.50 | | 2w-8=14 | | 8(z-3)+z=9(z-4)+12 | | 4x+6y=3750 | | 1.2x=14 | | 9(z-2)+4=9z+5 | | 9x-5x-x=3 | | 2(-1)-2(-1)-4= | | 6cos(3x)+3=4cos(3x)+4 | | 12(n+3)=3(12+4z) | | 10[sin^2(4x)]=5 | | 1.75+2y=0 | | 0.9z-17=1.5z-20 | | s-1/7 | | 10sin^2(4x)=5 | | 1.667x-1.334y=-1 | | 4x+6.2=10.6 | | 27^2m-n=1/9 |